Metal-rubber Bushing Test Research for Railway Vehicle - PENG Li-qun; LIN Da-wen; LI Xin; ZHANG Zhi-qiang; WANG Jin (机车电传动)
To settle the hard technical problem of test device rapid preparation and a mass of repeated detecting tests in metal-rubber bushing R&D for railway vehicle, a modular test device parameter design method based on PROE/EXCEL was presented. Modular test device was designed to test different structure product, which realized rapid design and assemblage with improving work efficiency for 35%, decreasing cost for 30%. With combination study of finite-element analysis and test, main factor affecting product stiffness was summarized and test results were validated consistent with calculation. The analysis result could guide product design and development to reduce test cost.